XALQARO PUL YUVISHGA QARSHI KURASHISH STANDARTLARINI TAKOMILLASHTIRISH: ULARNI AMALGA OSHIRISHNING USTUVOR YO‘NALISHLARI VA SAMARADORLIGINI OSHIRISH BO‘YICHA TAKLIFLAR - Baxromova, Laylo (YANGI DAVR ILM-FANI: INSON UCHUN INNOVATSION G‘OYA VA YECHIMLAR, 2026)
This article examines the priority directions for the implementation of international anti-money laundering standards and the ways to enhance their effectiveness. The study demonstrates that the central problem of the current AML regime lies in the persistent gap between formal compliance with international standards and their actual practical effectiveness. The author argues that improving AML standards requires stronger risk-based supervision, beneficial ownership transparency, institutional capacity, digital monitoring, and international cooperation.